Sequential intrapleural administration of fibrinolytic drugs and dornase alfa for empyema management. Treatment protocol based on its physicochemical stability - Carla Bastida (Farmacia Hospitalaria, 2020)
Objective: Intrapleural administration of fibrinolytics and dornase alfa has been shown in randomized studies to be able to reduce both the need for surgical debridement of empyema and the average hospital stay. However, its application in clinical practice is limited, probably due to the lack of protocols that simplify its administration. The present study aims to analyze the physicochemical stability of the simultaneous urokinase and dornase alfa administration for the subsequent development of a clinical practice use protocol. Method: In vitro stability test of urokinase, dornase alfa and a combination of both. Its stability was evaluated as (i) absence of particles, (ii) color variation and (iii) pH changes at times 0, 30 minutes, 1, 2 and 4 hours at 37 °C. Each sample was prepared and analyzed in triplicate. Results: Individual solutions of urokinase and dornase alfa showed slight changes in pH, finding no changes in either color or presence of suspended particles. The urokinase and dornase alfa combination was not stable after 2 hours, when turbidity emerged due to flocculation and phase separation. After 4 hours, precipitate formation was found. A pro tocol for clinical use was developed based on urokinase and dornase alfa sequential administration, since it was not possible to guarantee the physicochemical stability of the simultaneous administration of both drugs. Conclusions: The physicochemical stability data obtained does not allow to ensure a simultaneous administration of both drugs in a safe and effective way, thus a sequential administration protocol is proposed.